Beyond Technical Competence: Green Skills as a Pathway to Humanising Adult Education - De Angelis, Viviana (Lifelong Lifewide Learning, 2025)
In a global context marked by hyper-digitalization, technicization, polarization, and relational fragility, adult learning environments increasingly encounter misunderstanding, conflict, and hostility that undermine well-being in family, professional, and civic communities. This contribution argues that adult education must be reframed as a cultural and anthropological space where technical competences are integrated with ethical, relational, and ecological dimensions. Green skills, understood as dispositions to act consciously and responsibly toward oneself, others, and the living world, offer a bridge between professional training and holistic human development. Character education, grounded in the reflective cultivation of moral and civic virtues, contributes to shaping learning environments that regenerate relationships and promote peaceful coexistence. The article discusses pedagogical implications for designing more humane and sustainable educational ecosystems.